2000
DOI: 10.2135/cropsci2000.4051344x
|View full text |Cite
|
Sign up to set email alerts
|

Hormone‐Containing Products' Impact on Antioxidant Status of Tall Fescue and Creeping Bentgrass Subjected to Drought

Abstract: 10 grass species examined. Others reported that drought induced a significant increase in the antioxidant status This study was conducted to determine whether the plant endogein plants (Moran et al., 1994; Mukherjee and Choudhuri, nous antioxidant concentration is responsive to exogenous hormonecontaining products (HCPs) in two turfgrass species subjected to 1983; Smirnoff and Colombe, 1988 ). drought. Two-week-old seedlings of tall fescue (Festuca arundinacea Proper application of certain HCPs not only can im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(131 citation statements)
references
References 17 publications
10
113
1
7
Order By: Relevance
“…Similar observations were reported following the foliar application of seaweed extract on alfalfa plants at a rate of 300 g, which resulted in increased plant macro/micro elements such as N, P, K, Fe, Mn, and Zn [43]. These results suggest that seaweed extract may have the ability to improve stress tolerance [44] [45] by increasing nutrient uptake from the soil [46]. The beneficial effect of seaweed extract may be the result of many components working synergistically at different concentrations [47] especially those derived from Ascophyllum nodosum, which were reported to have high concentrations of total phenolics, a complex group known for its strong chelating activities [48] [49].…”
Section: Plant Tissue Chemical Characteristicssupporting
confidence: 83%
“…Similar observations were reported following the foliar application of seaweed extract on alfalfa plants at a rate of 300 g, which resulted in increased plant macro/micro elements such as N, P, K, Fe, Mn, and Zn [43]. These results suggest that seaweed extract may have the ability to improve stress tolerance [44] [45] by increasing nutrient uptake from the soil [46]. The beneficial effect of seaweed extract may be the result of many components working synergistically at different concentrations [47] especially those derived from Ascophyllum nodosum, which were reported to have high concentrations of total phenolics, a complex group known for its strong chelating activities [48] [49].…”
Section: Plant Tissue Chemical Characteristicssupporting
confidence: 83%
“…EDTA application to soil not only increased heavy metal availability in soils but also enhanced heavy metal content of the plant organs. This situation can be explained partly by their chelating capacity (Zhang and Schmidt 2000, Evangelou and Marsi 2001, Zhang et al 2003. When EDTA is added to soil containing heavy metals (Cu, Cd, Pb and Zn), EDTA complex the soluble form of heavy metal.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of micro-nutrients, especially Fe, in humic acids or their colloidal nature make them have a positive effect on the growth of various groups of micro-organisms which may excrete a range of vitamins, hormone-like growth substances and antibiotics that may further promote the growth (Nardi et al, 2002). In addition Zhang & Schmidt (2000), Nardi et al (2002) and Zhang & Ervin (2004) reported that humic acids contain cytokinins and have auxin-like activity. In addition, Rady and Osman (2011) stated that humic acid may stimulate plant growth by acting as a plant growth regulator.…”
Section: Morphological Charactersmentioning
confidence: 99%
“…These increments may due to the vigorous growth of plants resulted in the hormone-like activities of the humic acid through their involvement in increasing, photosynthesis, oxidative phosphorylation, protein synthesis, antioxidant and various enzymatic reactions. (Muscolo et al, 1993 andSchmidt, 2000). In addition, HA has been claimed to promote plant growth by increasing cell membrane permeability, oxygen uptake and photosynthesis, nutrient uptake, and root cell elongation (Russo & Berlyn, 1990, Böhme & Thi Lua, 1997and Nardi et al, 2002.…”
Section: Yield and Its Componentsmentioning
confidence: 99%